Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

The Wiki page on Twin Primes says

The pair $(m, m+2)$ is twin prime, iff $4((m-1)! + 1) \equiv -m \pmod {m(m+2)}$.

This is obviously connected to Wilson's Theorem. Can anybody provide a proof for that, along the lines of thought given here, Wilson's Theorem/Proofs/Prime modulus – another proof?

share|improve this question
2  
Use Chinese Remainder theorem. If $m$ is odd, then the right condition is equivalent to two formulas: $4((m-1)!+1) \equiv 0 \pmod m$ and $4((m-1)!+1)\equiv -2 \pmod {m+2}$. The case where $m$ is even needs to be dealt with separately. –  Thomas Andrews May 14 '12 at 19:43
add comment

2 Answers

up vote 5 down vote accepted

By Wilson's Theorem, if $m$ is prime, then $(m-1)!+1\equiv 0\pmod{m}$, and therefore $$4[(m-1)!+1]+m \equiv 0\pmod{m}.\tag{$1$}$$

If $m+2$ is prime, then $(m+1)!+1\equiv 0\pmod{m+2}$, again by Wilson's Theorem. But since $m+1\equiv -1\pmod{m+2}$, and $m\equiv -2\pmod{m+2}$, we have $(m+1)!\equiv (-1)(-2)(m-1)!\equiv 2(m-1)!\pmod{m+2}$, and therefore $$4[(m-1)!+1]+m \equiv 2(m+1)!+2+m+2\equiv 0\pmod{m+2}.\tag{$2$}$$ Since $m$ is odd, the numbers $m$ and $m+2$ are relatively prime, and therefore by $(1)$ and $(2)$ we have $4[(m-1)!+1]+m\equiv 0\pmod{m(m+2)}$.

The proof of the converse follows similar lines, this time using the fact that the Wilson condition is sufficient for primality.

share|improve this answer
    
Very nice. Not along the lines I asked for, but (even better) I learnt something else. Thank you. –  draks ... May 14 '12 at 21:43
add comment

Hint $\ $ Both directions can be quickly and easily proved simultaeneously using Wilson's theorem:

$\begin{eqnarray} \rm m\ prime &\iff&\rm\ mod\ m\!:\ &\rm\: 1+(m\!-\!1)! \equiv 0\iff 4(m\!-\!1)!+4\equiv 0\equiv -m \\ \rm m\!+\!2\ prime &\iff&\rm mod\ m\!+\!2\!:\ &\rm\: 1+(m\!+\!1)!\equiv 0\iff 4(m\!-\!1)!+4 \equiv 2\equiv -m\\ \rm & &\rm because &\rm \!\!\!\!2(1+(m\!+\!1)!)\:\ =\:\ 2\: +\: 4(m\!-\!1)! + 2(m\!+\!2)(m\!-\!1)(m\!-\!1)! \\ & &\rm because &\rm\!\!\!\! 2(m\!+\!1)! = 2(m\!+\!1)m(m\!-\!1)! = (4\!+\!2(m\!+\!2)(m\!\!-\!1)\!)(m\!-\!1)! \\ \end{eqnarray}$

Remark $ $ Explicitly, by 2nd prior: $\rm\:1+(m\!+\!1)!\equiv 0\iff 4(m\!-\!1)!\equiv -2\pmod{m\!+\!2},\:$ which yields the equivalence directly above it. Note that no ingenuity is required in the second case, other than knowing to rewrite $\rm\:(m+1)!\:$ in terms of $\rm\:(m-1)!\:$ The rest is straightforward arithmetic modulo $\rm\:m+2\:$ (which I have presented it in a form most amenable to mental verification).

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.